Developments in UK police wellbeing: A review of blue light wellbeing frameworks. (March 2022) - Phythian, Rebecca; Birdsall, Nathan; Kirby, Stuart; Cooper, Emily; Posner, Zoe; Boulton, Laura
Policing demands are widely acknowledged to negatively impact on the physical and mental health of police officers and staff. Research has documented the need for greater insight into the stressors and trauma that impact police officers, with a current national drive towards enhancing the police wellbeing agenda: namely, Oscar Kilo and the National Wellbeing Service. To understand the current wellbeing strategies in place, 34 Blue Light Wellbeing Frameworks were analysed. A mixed methods approach was adopted: quantitative data was descriptively examined, with thematic analyses employed to explore the qualitative data. Findings from the review highlight developments in police wellbeing, as well as areas for future development.